2020
DOI: 10.1038/s41467-020-19585-0
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota-directed fibre activates both targeted and secondary metabolic shifts in the distal gut

Abstract: Beneficial modulation of the gut microbiome has high-impact implications not only in humans, but also in livestock that sustain our current societal needs. In this context, we have tailored an acetylated galactoglucomannan (AcGGM) fibre to match unique enzymatic capabilities of Roseburia and Faecalibacterium species, both renowned butyrate-producing gut commensals. Here, we test the accuracy of AcGGM within the complex endogenous gut microbiome of pigs, wherein we resolve 355 metagenome-assembled genomes toget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 65 publications
0
37
0
3
Order By: Relevance
“…Thereby, specific metabolites are produced by specialized microbes. 55 Interestingly, a recent study in pigs demonstrated that a microbiota-accessible fiber elicited both targeted and secondary metabolic shifts in the microbiota, 56 suggesting that metabolic exchanges and cross-feeding also contribute to metabolite production in response to dietary fiber. Although insoluble fibers are usually considered to be less metabolizable by the gut microbes, changes in enzymatic pathways and metabolite production, such as linoleic acid, nicotinate and nicotinamide, glycerophospholipid, glutathione, sphingolipid, as well as valine, leucine, and isoleucine metabolic pathways were observed after cellulose intake in animal models.…”
Section: Dietary Fiber and The Gut Microbiotamentioning
confidence: 99%
“…Thereby, specific metabolites are produced by specialized microbes. 55 Interestingly, a recent study in pigs demonstrated that a microbiota-accessible fiber elicited both targeted and secondary metabolic shifts in the microbiota, 56 suggesting that metabolic exchanges and cross-feeding also contribute to metabolite production in response to dietary fiber. Although insoluble fibers are usually considered to be less metabolizable by the gut microbes, changes in enzymatic pathways and metabolite production, such as linoleic acid, nicotinate and nicotinamide, glycerophospholipid, glutathione, sphingolipid, as well as valine, leucine, and isoleucine metabolic pathways were observed after cellulose intake in animal models.…”
Section: Dietary Fiber and The Gut Microbiotamentioning
confidence: 99%
“…Since its first introduction in 2004 5 , mass spectrometry (MS)-based metaproteomics has quickly emerged as a powerful tool to functionally characterize a broad variety of microbial communities in situ. This allows a direct link to the phenotypes on a molecular level and shows the adaptation of the microorganisms to their specific environment 6 . Metaproteomics thus complements other meta-omic approaches such as metagenomics and metatranscriptomics, as these only have the exploratory power to assess the diversity and functional potential of microorganisms, but cannot observe their actual phenotypes 7 .…”
Section: Mainmentioning
confidence: 99%
“…This allows a direct link to the phenotypes on a molecular level and shows the adaptation of the microorganisms to their specific environment 6 . Metaproteomics thus complements other meta-omic approaches such as metagenomics and metatranscriptomics, as these only have the exploratory power to assess the diversity and functional potential of microorganisms, but cannot observe their actual phenotypes 7 .…”
Section: Mainmentioning
confidence: 99%
“…Taking advantage of the mannan‐specific esterase capability of butyrate‐producing bacteria, such as Roseburia and Faecalibacterium species, an acetylated galactoglucomannan was tested as a microbiota‐directed food in a porcine model and demonstrated additional non‐mannolytic metabolic effects, specifically influencing short‐chain fatty acid production 7 .…”
Section: Dietary Targetsmentioning
confidence: 99%